Cosmological constraints on bulk viscous f(Q, T) gravity. Issue 5 (30th March 2022) - Sokoliuk, Oleksii; Baransky, Alexander
Abstract: In the General Theory of Relativity (GR) gravitational interactions are described by the scalar Ricci curvature. But there exists another class of modified gravity theories equivalent to GR, described by the torsion tensor or non‐metricity scalar. One of such theories, investigated in this paper is f ( Q, T ) gravity, built from the arbitrary function of non‐metricity scalar non‐minimally coupled to the trace of stress‐energy tensor. Current work is aimed on the linear f ( Q, T ) = α Q + β T gravity, where α and β are free MOG parameters to be varied. As well, we assume that the fluid is bulk‐viscous with pressure p ‾ = p − 3 ζ H and the bulk viscosity parameter ζ = ζ 0 + ζ 1 H + ζ 2 ( H ˙ / H + H ) . From the modified Einstein Field Equations (EFE's) we obtain the Hubble parameter analytically and constrain free parameters of the model through the MCMC sampling of 57 recent Hubble parameter observations. We found that computed Hubble rate for our model from MCMC sampling converges with the observational data at the ± 1 σ confidence level. To examine the current accelerated expansion rate of the universe in details we use the statefinder diagnostics. Besides, to distinguish Λ CDM and our model we use Om ( z ) analysis.